The OSCE and Human Dimension in the Republic of Georgia - Jan Brodowski (Politeja, 2025)
The article focuses on the OSCE’s actions in the human dimension, using Georgia as a case study of a country facing constant challenges. The research aligns with the functionalist school, highlighting the essential role of international organizations in tasks beyond state capabilities. Research methods include archival research, interviews during a study visit to Georgia, election observation missions, and analysis of OSCE documents, focusing on the 2023-2024 political crisis. The OSCE’s presence and support have been crucial for progress in areas like rule of law, institution building, and electoral transparency. However, although the OSCE has been present and active in that region, its recommendations are not fully implemented by the Georgian government. Georgian authorities have often contradicted OSCE recommendations, particularly in upholding civil rights and ensuring transparent elections.